Reform Through A Good Governance Approach: A Policy Study In Indonesia - Anton Nugroho (LPPM Universitas PGRI Sumatera Barat, 2023)
This study examines the reform of Indonesia’s national defense management through a good governance framework, positioning institutional governance as a critical determinant of defense effectiveness. The growing complexity of multidimensional security threats requires defense systems that are not only operationally capable but also institutionally transparent, accountable, and cross-sectorally coordinated. Despite ongoing public sector reforms, the integration of good governance principles into defense management reveals a persistent gap between normative design and implementation practice.Using a qualitative descriptive-analytical approach, this study relies on document analysis of defense policies, regulations, and governance literature. Content analysis and policy analysis are employed to assess the alignment between the principles of transparency, accountability, participation, rule of law, and policy effectiveness and the institutional practices of defense management.The findings indicate that reforms have strengthened civilian–military functional separation, strategic planning mechanisms, and formal accountability systems. However, defense governance continues to face structural constraints, including fragmented authority, weak intersectoral coordination, and limited integration between planning and implementation. At the cultural level, hierarchical organizational norms slow the adoption of participatory and transparent governance practices. The study demonstrates that the relationship between good governance and defense effectiveness is indirect and mediated by the quality of institutional management reform. Its primary contribution lies in advancing a conceptual linkage between public governance and defense sector performance while offering policy recommendations centered on institutional integration and results-based accountability.